2022
DOI: 10.55519/jamc-03-10382
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Pulmonary Thrombosis in Patients With Coronavirus-19 Disease; Case Series and Review of the Literature

Abstract: Background: Coronavirus disease 19 (COVID-19) is a viral disease caused by SARS-CoV-2. There is an increased incidence of a thromboembolic phenomenon in patients with COVID-19 infection. Pulmonary embolism is the most common thrombotic presentation in COVID-19 patients. Extra-pulmonary thrombosis is an unusual thrombotic complication of COVID-19 disease. Methods: This study was conducted at The Aga Khan University Hospital from June-July’2021. Patients clinical and laboratory findings, treatment, and outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In our case, lower GSS was more likely to result in SFS (p = 0.008). Multiple other studies investigating the reliability of the score have also shown a good correlation between GSS and SFS [3,4,[12][13][14]. S-ReSCS is a score more focused on the structural complexity of the stones.…”
Section: Discussionmentioning
confidence: 94%
“…In our case, lower GSS was more likely to result in SFS (p = 0.008). Multiple other studies investigating the reliability of the score have also shown a good correlation between GSS and SFS [3,4,[12][13][14]. S-ReSCS is a score more focused on the structural complexity of the stones.…”
Section: Discussionmentioning
confidence: 94%
“…Vitamin B12 deficiency and folate deficiency are known causes of megaloblastic anemia 78,79) and subacute association spinal cord degeneration 80) , but even without these conditions, they are known to cause cognitive decline 81) . Folic acid deficiency and associated elevated homocysteine levels are also thought to cause dementia and affective disorders such as depression 82) .…”
Section: Vitamin Intake and Dementia Preventionmentioning
confidence: 99%